Microstructural Evolution and High-Performance Giant Dielectric Properties of Lu3+/Nb5+ Co-Doped TiO2 Ceramics - Noppakorn Thanamoon (MDPI AG, 2021)
Giant dielectric (GD) oxides exhibiting extremely large dielectric permittivities (ε’ > 104) have been extensively studied because of their potential for use in passive electronic devices. However, the unacceptable loss tangents (tanδ) and temperature instability with respect to ε’ continue to be a significant hindrance to their development. In this study, a novel GD oxide, exhibiting an extremely large ε’ value of approximately 7.55 × 104 and an extremely low tanδ value of approximately 0.007 at 103 Hz, has been reported. These remarkable properties were attributed to the synthesis of a Lu3+/Nb5+ co-doped TiO2 (LuNTO) ceramic containing an appropriate co-dopant concentration. Furthermore, the variation in the ε’ values between the temperatures of −60 °C and 210 °C did not exceed ±15% of the reference value obtained at 25 °C. The effects of the grains, grain boundaries, and second phase particles on the dielectric properties were evaluated to determine the dielectric properties exhibited by LuNTO ceramics. A highly dense microstructure was obtained in the as-sintered ceramics. The existence of a LuNbTiO6 microwave-dielectric phase was confirmed when the co-dopant concentration was increased to 1%, thereby affecting the dielectric behavior of the LuNTO ceramics. The excellent dielectric properties exhibited by the LuNTO ceramics were attributed to their inhomogeneous microstructure. The microstructure was composed of semiconducting grains, consisting of Ti3+ ions formed by Nb5+ dopant ions, alongside ultra-high-resistance grain boundaries. The effects of the semiconducting grains, insulating grain boundaries (GBs), and secondary microwave phase particles on the dielectric relaxations are explained based on their interfacial polarizations. The results suggest that a significant enhancement of the GB properties is the key toward improvement of the GD properties, while the presence of second phase particles may not always be effective.